On Corporate Accountability: Lead, Asbestos, and Fossil Fuel Lawsuits. (August 2015) - Shearer, Christine
This paper examines the use of lawsuits against three industries that were eventually found to be selling products damaging to human heath and the environment: lead paint, asbestos, and fossil fuels. These industries are similar in that some companies tried to hide or distort information showing their products were harmful. Common law claims were eventually filed to hold the corporations accountable and compensate the injured. This paper considers the important role the lawsuits played in helping establish some accountability for the industries while also noting the limitations of the lawsuits. It will be argued that the lawsuits helped create pressure for government regulation of the industries' products but were less successful at securing compensation for the injured. Thus, the common law claims strengthened and supported administrative regulation and the adoption of industry alternatives more than they provided a means of legal redress.